Analisis Bahan Ajar Anatomi Fisiologi Tubuh Manusia (Karya Daniel Suranta Ginting, Et Al) - Waruwu, Sela Marselina; Zega, Listen Arahan; Harefa, Lindawati; Ndraha, Fita Kristiani; Lase, Natalia Kristiani (Lembaga Intelektual Muda (LIM) Maluku, 2024)
In the world of education, teaching materials have a crucial role in the teaching and learning process. Teaching materials include all types of materials used by teachers or instructors to support learning activities in the classroom. Thus, teaching materials are prepared to achieve the desired goals, namely mastering the necessary competencies or subcompetencies along with all their aspects. The purpose of this study is to analyze the identity, content and advantages and disadvantages of a teaching material. The method used in this study is the research method of the pustka study. The results of this study are teaching materials on Physiological Anatomy of the Human Body